2021
DOI: 10.3390/jfmk6040091
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sonographer Experience on Skeletal Muscle Image Acquisition and Analysis

Abstract: The amount of experience with ultrasonography may influence measurement outcomes while images are acquired or analyzed. The purpose of this study was to identify the interrater reliability of ultrasound image acquisition and image analysis between experienced and novice sonographers and image analysts, respectively. Following a brief hands-on training session (2 h), the experienced and novice sonographers and analysts independently performed image acquisition and analyses on the biceps brachii, vastus laterali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Brightness mode ultrasound is a reliable tool for measuring skeletal muscle morphology ( Carr et al, 2021 ; Van Hooren, Teratsias & Hodson-Tole, 2020 ; Kwah et al, 2013 ; May, Locke & Kingsley, 2021 ; Rosenberg et al, 2014 ; De Souza Silva et al, 2018 ). In the current study, manual ultrasound analyses indicated good reliability when assessing muscle architecture ( i.e ., FA and FL) (ICC 2,1 = 0.75–0.86) with low absolute error (SEM% = 9.99–13.69).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Brightness mode ultrasound is a reliable tool for measuring skeletal muscle morphology ( Carr et al, 2021 ; Van Hooren, Teratsias & Hodson-Tole, 2020 ; Kwah et al, 2013 ; May, Locke & Kingsley, 2021 ; Rosenberg et al, 2014 ; De Souza Silva et al, 2018 ). In the current study, manual ultrasound analyses indicated good reliability when assessing muscle architecture ( i.e ., FA and FL) (ICC 2,1 = 0.75–0.86) with low absolute error (SEM% = 9.99–13.69).…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous ( Van Hooren, Teratsias & Hodson-Tole, 2020 ; Kellis et al, 2009 ) works do suggest ultrasound to be a valid technique to assess muscle architecture. While the automatic tool used in the present study is valid when compared to the manual method, future studies may wish to validate this technique against other imaging modalities ( i.e ., MRI) and using different ultrasound operators ( Carr et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary author (sonographer with >200 hrs hamstring scanning experience) performed all assessments and collated and digitised all sonograms for subsequent analysis. Experienced sonographers, when compared to novice sonographers, generate higher quality sonograms which permits reliable skeletal muscle image acquisition and architectural analysis [ 34 ].…”
Section: Methodsmentioning
confidence: 99%